Relationship between power strength and anaerobic power index as a clear picture of the effect of strength training among young soccer elite players - Zerf, M.; Kerroum, M. A.; Bouabdellah, S. B. A (Slobozhanskyi herald of science and sport, 2019)
Purpose: muscle contraction has both mechanical to produce movement and metabolic properties to produce energy. However, manipulation of strength training planes (horizontal or vertical) subject to be an important training strategy to develop soccer-specific power-based actions. Depending on mode of exercise and more important the energy demands.